Properties of Asphalt Mixtures Using Reclaimed Asphalt Containing Polymer-Modified Binder and Technicoeconomical Considerations of Their Use - Jan Mikolaj; Frantisek Schlosser; Lubos Remek; Martin Pitoňák; Juraj Šrámek (Advances in Materials Science and Engineering)
The article summarises findings from laboratory testing of asphalt mixtures using reclaimed asphalt containing polymer-modified binder and subsequent technicoeconomical considerations of their use in pavement management system. Tested mixtures had 0%, 15%, and 40% content of reclaimed asphalt (RA) containing polymer-modified bitumen (PMB) obtained by milling from surfacing layers of existing PA, AC11, and SMA11 pavement layers. A complete description of these mixtures is given, and testing methods used are described. The mixtures were tested for air void content, ITSR water sensitivity test, plastic deformation wheel tracking test, stiffness of the tested mixtures, and two-point bending test to ascertain fatigue. Concise and succinct conclusions from laboratory testing are derived and used as an input in the second part of the article. It is found that the addition of RA containing PMB increased stiffness modulus of the final mixture, which increases resistance to plastic deformation and leads to higher brittleness at low temperatures. It is found that virgin PMB also increases fatigue resistance as opposed to PMB content from reclaimed materials. In the second part of the article, findings from laboratory testing are addressed in the context of their practical use in pavement management. The key element identified, having a direct impact on pavement performance models, was the stiffness modulus for mixtures with different PMB-reclaimed asphalt contents. A method is described to evaluate pavement construction properties related to wearing course materials via the pavement performance model. Practical use of this method is described and applied in a case study. In this case study, the proposed method is used to evaluate the issues regarding practical use of asphalt mixtures with different ratios of reclaimed asphalt containing PMB and economic implications of their use. It is found that pavement performance of surfacing mixtures with reclaimed asphalt containing PMB is significantly better for plastic deformation at the cost of earlier initiation and progression of surface distress due to cracking and potholing. This paper suggests that due to cracking and potholing, periodic maintenance costs increase for pavements with reclaimed asphalt material containing PMB; however, they are outweighed by lower procurement cost and longer life expectancy due to slower plastic deformation of the pavement.